A Hydrodynamic Modelling Framework for Strangford Lough Part 1: Tidal Model - Louise Kregting; Björn Elsäßer (Journal of Marine Science and Engineering, 2014)
Hydrodynamic models are a powerful tool that can be used by a wide range of end users to assist in predicting the effects of both physical and biological processes on local environmental conditions. This paper describes the development of a tidal model for Strangford Lough, Northern Ireland, a body of water renowned for the location of the first grid-connected tidal turbine, SeaGen, as well as the UK’s third Marine Nature Reserve. Using MIKE 21 modelling software, the development, calibration and performance of the model are described in detail. Strangford Lough has a complex flow pattern with high flows through the Narrows (~3.5 m/s) linking the main body of the Lough to the Irish Sea and intricate flow patterns around the numerous islands. With the aid of good quality tidal and current data obtained throughout the Lough during the model development, the surface elevation and current magnitude between the observed and numerical model were almost identical with model skill >0.98 and >0.84 respectively. The applicability of the model is such that it can be used as an important tool for the prediction of important ecological processes as well as engineering applications within Strangford Lough.